Cerebellar Anaplastic Astrocytoma in an Adult with Neurofibromatosis Type 1: Case Report and Review of Literature - Brokinkel, Benjamin; Schober, Otmar; Ewelt, Christian; Heindel, Walter; Hargus, Gunnar; Stummer, Walter; Holling, Markus; Wölfer, Johannes (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background Low-grade gliomas (e.g., pilocytic astrocytomas) are frequently found in patients with neurofibromatosis type 1 (NF1). Whereas most of those lesions are located supratentorially, cerebellar manifestations are described in < 1%. Malignant variants like glioblastoma and anaplastic astrocytoma (AA) are only rarely observed in NF1 patients. Thus, cerebellar AA is very infrequent and has not yet been described in an adult NF1 patient.Clinical Presentation We present the case of a 54-year-old male patient with von Recklinghausen disease who had a diffuse contrast-enhancing cerebellar mass that was resected guided by aminolevulinic acid (ALA)-fluorescence. Histopathological analyses revealed an AA with lack of pilocytic features or O6-methylguanine-DNA methyltransferase (MGMT) promoter hypermethylation. Due to the proximity of the tumor to the brainstem, adjuvant temozolomide chemotherapy was administered rather than first-line radiotherapy. Although the patient recovered quickly after the operation and tumor progression was ruled out in follow-up magnetic resonance imaging (MRI), the patient strongly deteriorated during a 16-month follow-up, and MRI revealed severe leukoencephalopathy. Extensive electrophysiological and radiological examination revealed a neurodegenerative disease of unknown etiology. Finally, the patient's condition improved receiving levodopa.Conclusions A literature search yielded only one previously published case of an AA in a 9-year-old girl with NF1. Tumor control after resection was achieved in both patients; however, the patient in the mentioned report received radiation instead of temozolomide. In spite of different adjuvant therapies, tumor control for at least 16 months was achieved in both published cases. Thus, even though the role of adjuvant treatment options remains to be further elucidated, surgery is the appropriate therapy in these uncommon tumors providing mass reduction and histological diagnosis as well as tumor control.
Keywords: anaplastic astrocytoma; cerebellum; neurofibromatosis; Recklinghausen disease